Phosphorylation of ETS Transcription Factor ER81 in a Complex with Its Coactivators CREB-Binding Protein and p300 - Papoutsopoulou, Stamatia (American Society for Microbiology, 2000)
The ETS protein ER81 is a DNA-binding factor capable of enhancing gene transcription and is implicated in cellular transformation, but presently the mechanisms of its actions are unclear. In this report, ER81 is shown to coimmunoprecipitate with the transcriptional coactivator CREB-binding protein (CBP) and the related p300 protein (together referred to as CBP/p300). Moreover, confocal laser microscopic studies demonstrated that ER81 and p300 colocalized to nuclear speckles. In vitro and in vivo interaction studies revealed that ER81 amino acids 249 to 429, which encompass the ETS DNA-binding domain, are responsible for binding to CBP/p300. However, mutation of a putative protein-protein interaction motif, LXXLL, in the ETS domain of ER81 did not affect interaction with CBP/p300, whereas DNA binding of ER81 was abolished. Furthermore, two regions within CBP, amino acids 451 to 721 and 1891 to 2175, are capable of binding to ER81. Consistent with the physical interaction between ER81 and the coactivators CBP and p300, ER81 transcriptional activity was potentiated by CBP/p300 overexpression. Moreover, an ER81-associated protein kinase activity was enhanced upon p300 overexpression. This protein kinase phosphorylates ER81 on serines 191 and 216, and mutation of these phosphorylation sites increased ER81 transcriptional activity in Mv1Lu cells but not in HeLa cells. Altogether, our data elucidate the mechanism of how ER81 regulates gene transcription, through interaction with the coactivators CBP and p300 and an associated kinase that may cell type specifically modulate the ability of ER81 to activate gene transcription.